2021
DOI: 10.1002/smll.202105424
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguration of Amorphous Complex Oxides: A Route to a Broad Range of Assembly Phenomena, Hybrid Materials, and Novel Functionalities

Abstract: materials that are freestanding either at a stage in their fabrication, in their final state, or both. [1] NMs with thicknesses in the range of a few nanometers to a few hundred nanometers can be isolated from their substrates through synthesis and processing techniques that have become established in the last 20 years. [1][2][3][4][5] The lateral dimensions of NMs are at least two orders of magnitude larger than their thickness, making them a distinctive platform from 0D, 1D, and bulk materials. [6] NMs enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…We have earlier shown that self-assembly [40] of ultra-thin films or nanomembranes into 3D structures [41] serves as a sensitive probe to measure film stress evolution [42,43] during the structural transformation of metastable films, such as amorphous complex oxides. [44] We use this approach to calculate the average stress in the electrodeposited Au films and stress/strain profile in the helix in x, y, and z directions.…”
Section: Stress Distributions and Strain In Helical Heterostructure R...mentioning
confidence: 99%
“…We have earlier shown that self-assembly [40] of ultra-thin films or nanomembranes into 3D structures [41] serves as a sensitive probe to measure film stress evolution [42,43] during the structural transformation of metastable films, such as amorphous complex oxides. [44] We use this approach to calculate the average stress in the electrodeposited Au films and stress/strain profile in the helix in x, y, and z directions.…”
Section: Stress Distributions and Strain In Helical Heterostructure R...mentioning
confidence: 99%